ISLAMIC EDUCATION SUPERVISION TECHNIQUES AT AL-FALAH ISLAMIC BOARDING SCHOOL, KRUI, WEST COAST, LAMPUNG - Dirgatama, Erwanda; Fitryansyah, Allya; Yani, Intan Safitri; Subandi, Subandi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic education plays a strategic role in shaping the character and morals of the younger generation, with pesantren (Islamic boarding schools) being one of the key institutions. However, efforts to improve the quality of learning in pesantren face various challenges, particularly in the implementation of ineffective educational supervision. Preliminary research findings indicate that the pesantren under study lacks a structured and systematic supervision system. This is due to supervision that is considered to not meet the expected standards, which consequently impacts the quality of education, leading to less optimal learning outcomes. This study aims to identify effective supervision techniques to enhance the quality of learning in Islamic educational institutions. Using a qualitative approach through a case study method, this research was conducted at Pesantren Al-Falah in Krui Pesisir Barat Lampung. Data were gathered through in-depth interviews and participant observation, which were then analyzed using content analysis techniques to identify key themes related to supervision techniques. The findings classify supervision techniques into two main categories: individual supervision and group supervision. The study emphasizes the importance of active participation from leaders and supervisors to support the optimal implementation of supervision techniques. Furthermore, integrating supervision techniques with Islamic educational values is necessary to build a culture of sustainable learning. Therefore, implementing a structured, integrated, and Islam-based supervision program can significantly improve educational quality, while also serving as a reference for the development of future supervision policies.